Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) a + (-25)
Thay a = -15 ta có :
-15 - 25 = -40
b) (-87) + b
Thay b = 13 ta có :
-87 + 13 = -74
Vậy..........
Bài 1:
a. A = 125 . (-61) . (-2)3 . (-1)24
= 125. (-8). (-61) . 124
= 125. 8. 61.1
= 1000. 61 = 61000
b. B = 136. (-47) + 36.47
= (-136).47 + 36.47
= 47. (-136 + 36)
= 47. (-100) = -4700
c. C = (-48).72 + 36.(-304)
= (-96).36 + 36. (-304)
= 36. (-96-304)
= 36. (-400) = -14400
d. D = 87.(13-18) - 13.(87 + 18)
= 87.13 - 87.18 - 13.87 - 13.18
= - 87.18 - 18.13
= - 18.(87+13)
= - 18.100 = -1800
Bài 2:
a. TH1: x - 2 = 0 => x = 2
TH2: 5-x = 0 => x = 5
b. |x| = 56 - 23 = 33 => x = cộng trừ 33
c. 3 - (17-x) = 289 - (36 + 289)
=> 3 - 17 + x = 289 - 289 - 36
=> -14 + x = -36
=> x = -36 - (-14) = -22
1.
a. A = 125 . (-61) . (-2)3 . (-1)24
= 125.(-61).(-8).1
= (-8.125).(-61)
= -1000.(-61)
= 61000
b. B = 136 . (-47) + 36 . 47
=-136.47+36.47
=47(-136+36)
= 47.(-100)
= -4700
2.
a. (x - 2) . (5 - x) = 0
=> x - 2 = 0 hoặc 5 - x = 0
=> x = 2 hoặc x = 5
b. 56 - lxl = 23
=> |x| = 33
=> x = 33 hoặc x = -33
c. 3 - (17 - x) = 289 - (36 + 289)
=> 3 - 17 + x = 289 - 36 - 289
=> -14 + x = -36
=> x = -22
=87.13-87.39-13.87-13.39
=13.(87-87)-39.(87+13)
=13.0-39.100
=0-3900
=-3900
a) -65 .( 87 - 17 ) -87 .( 17 - 65 )
= ( - 65 ) . 87 + 17 - 87 . 17 + 65
= { ( - 65 ) + 65 } . 87 + 17
= 0 . 87 + 17
= 17
b) -215 . [ 14 + ( -236 ) ] + 215 . ( 14 - 236 )
= -215 . 14 + ( - 236 ) + 215 . 14 - 236
= [ ( - 215 ) + 215 ] . 14 + { ( - 236 - 236 }
= 0 . 14 + 0
= 0
x + 87 + 13 = 200
x + 100 = 200
x = 200 - 100
x = 100
Vậy x trong biểu thức = 100
thay số => -87+13=-74